Psychological and pedagogical support of families raising children with disabilities - Serenej V. V. (Interactive science, 2019)
the article describes the main difficulties of child-parent relations in families where children with disabilities are raised, the content of psychological and pedagogical support of families raising children with disabilities is revealed. The purpose and main tasks of psychological and pedagogical support of families with children with disabilities are formulated. Stages of psychological and pedagogical support of the family raising children with disabilities, and also the main directions of work with a family within the Centers of early help and support are designated.
Keywords: психолого-педагогическое сопровождение; дети с ОВЗ; children with disabilities; psychological and pedagogical support; трудности детско-родительских отношений; этапы психолого-педагогического сопровождения; difficulties of child-parent relations; stages of psychological and pedagogical support